Ecosystem feedbacks contribute to geographic variation in plant–soil eco‐evolutionary dynamics across a fertility gradient. (7th January 2019) - Van Nuland, Michael E.; Ware, Ian M.; Bailey, Joseph K.; Schweitzer, Jennifer A.
Abstract: Plant species that occur in different soil nutrient environments often vary in plant functional traits that affect soil nutrient cycling, creating positive feedbacks that reinforce nutrient availability. Variation in such nutrient feedbacks could affect plant fitness, but few studies have explored the eco‐evolutionary dynamics of within‐species nutrient feedbacks, and the role that soil communities may play in mediating plant evolutionary responses. We investigated whether a widespread Populus species regulates soil fertility, resulting in positive nutrient feedbacks that influence population divergence. Here, we combined field observations, a reciprocal transplant experiment, and soil community sequencing to test how nutrient feedbacks might facilitate plant adaptation to soil environments. We find that: (1) Plant populations exist along a soil fertility gradient in the field and display trait variation consistent with positive nutrient feedbacks, (2) populations assemble distinct soil prokaryotic communities that are structured by soil chemistry, (3) populations show inconsistent patterns of local adaptation to their soil communities, however (4) genetic variation in plant–soil interactions reinforces soil nutrient differences. Soil communities may mediate variation in plant adaptation across a soil fertility gradient such that plant–soil interactions reinforce positive nutrient feedbacks. Identifying the eco‐evolutionary links between plant trait variation, soil nutrients and microbial communities demonstrates that plants modify and adapt to soil environments. These results support the hypothesis that eco‐evolutionary feedbacks may result when plant–soil interactions (eco) affect ecosystem‐level processes that sustain population‐level feedbacks and selective gradients (evo). A plain language summary is available for this article. Abstract : Plain Language Summary